Koillisen Siperian tšuktšien henkilölaulu musiikillisen ajattelun käännekohtana. Lectio Praecursoria - Pia Siirala (The Sibelius Academy of the University of the Arts Helsinki, 2024)
Becoming acquainted with the music of the indigenous people of north-eastern Siberia has been a turning point in my perception of music, and has made me question what music is at a fundamental level. In my field trips to north-eastern Siberia I studied the music of the Chukchi and other indigenous peoples. This doctoral project centered on my particular interest in the Chukchi Personal Song, in which music is part of their persona.